Development of Muhammadiyah Teaching Materials Based on Learning Innovation - Ismail Syakban; Dewi Rahmayani; Syarifah Sriwahyuni; Zaniar Zaniar (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2026)
This research aims to develop teaching materials for Muhammadiyah courses that are oriented towards digital learning innovation and blended learning in the Muhammadiyah Higher Education environment. This research is motivated by the still dominant use of conventional lecture methods and the limitations of the use of interactive digital media in Muhammadiyah learning. Based on initial observations of three lecturers and twenty students of the Islamic Religious Education Study Program at the University of Muhammadiyah West Sumatra, it was found that most students considered the learning process less interesting, while lecturers still faced obstacles in integrating technology-based learning approaches effectively. This research uses a Research and Development (R&D) approach with the Borg and Gall model which is adapted into four stages, namely needs analysis, product design, limited trials, and evaluation and revision. The product developed is different from existing teaching materials because it integrates progressive Islamic values, interactive digital content, reflective learning activities, and blended learning models that combine synchronous and asynchronous learning. Research data was collected through observation, interviews, questionnaires, and limited product trials. Student engagement is measured through indicators of participation, interaction, learning motivation, and assignment completion during learning implementation. The results of the study show that the teaching materials developed are able to increase student participation and strengthen understanding of the ideological values and praxis of Muhammadiyahan. However, this study also found several limitations, such as the limited number of participants, the context of research that was only conducted at one institution, and the difference in the level of digital literacy between lecturers and students. These findings show that the development of digital teaching materials based on Progressive Islamic values has the potential to increase the relevance and effectiveness of Muhammadiyah learning, although broader testing is needed to assess the sustainability and generalization of research results.